Tuning charge transport across junctions of ferrocene-containing polymer brushes on ITO by controlling the brush thickness and the tether lengths. (December 2017) - Gan, Lu; Suchand Sangeeth, C.S.; Yuan, Li; Jańczewski, Dominik; Song, Jing; Nijhuis, Christian A.
Graphical abstract: Highlights: We fabricated junctions with ferrocene-containing polymer brushes between two electrodes. Conduction mechanism of the junctions can be switched from tunnelling to hopping. The direction of rectification can be controlled via the polymer brush thickness. Redox-active polymer brushes are interesting for nanoscale electronics. Abstract: This paper describes the electrical characteristics of junctions of ferrocene (Fc)-containing polymer brushes (PBs) grafted on indium tin oxide (ITO) bottom electrodes contacted with eutectic gallium indium (EGaIn) top electrodes. We studied the charge transport phenomena across these junctions as a function of the PB thickness as well as the length of the tether ( i.e., an alkyl chain side linker) between the Fc units and the polymethyl methacrylate backbone. Junctions with PBs with a thickness of <20 nm do not rectify while those junctions with PBs with a thickness of >20 nm do rectify. Temperature dependent charge transport measurements revealed that the charge transport mechanism is dominated by space charge limited conduction (SCLC).